2000
DOI: 10.1074/jbc.m002149200
|View full text |Cite
|
Sign up to set email alerts
|

The Immunologically Protective P-4 Antigen ofLeishmania Amastigotes

Abstract: The purified membrane-associated Leishmania pifanoi amastigote protein P-4 has been shown to induce protective immunity against infection and to elicit preferentially a T helper 1-like response in peripheral blood mononuclear cells of patients with American cutaneous leishmaniasis. As this molecule is potentially important for future vaccine studies, the L. pifanoi gene encoding the P-4 membrane protein was cloned and sequenced. Southern blot analyses indicate the presence of six tandemly arrayed copies of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…It has shown that expression of this nuclease upregulated significantly in response to purine starvation [13, 17] which is consistent with the opinion that class I nuclease enzyme plays a vital role in providing purines for growth and development of Leishmania parasites. Since there is no a homologue enzyme with similar properties in mammalian tissues, this enzyme can serve as a chemotherapeutic target for selective targeting of Leishmania during infection [11].…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…It has shown that expression of this nuclease upregulated significantly in response to purine starvation [13, 17] which is consistent with the opinion that class I nuclease enzyme plays a vital role in providing purines for growth and development of Leishmania parasites. Since there is no a homologue enzyme with similar properties in mammalian tissues, this enzyme can serve as a chemotherapeutic target for selective targeting of Leishmania during infection [11].…”
Section: Resultssupporting
confidence: 80%
“…P-4 is a single-stranded specific class I nuclease that was identified initially in L. amazonensis [16] and then characterized in L. pifanoi by Kar et al [17]. Recently, we isolated a class I nuclease gene from amastigotes of L. major [18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter include the following: 1) a Ն40-kDa bi-functional, 3Ј-nucleotidase/nuclease anchored in the cell surface membranes of several pathogenic species of Leishmania (i.e. L. donovani and Leishmania mexicana (5,7,9)) as well as Crithidia luciliae (8), and 2) a P-4 antigen/nuclease specifically localized to the endoplasmic reticulum of Leishmania pifanoi amastigote forms (39). In addition, a related P1/S1 gene homolog has been reported from an Iranian isolate of L. major, but no functional enzyme activity or subcellular localization was demonstrated for the product of that gene (22).…”
Section: Discussionmentioning
confidence: 99%
“…This analysis, shown in Figure 1C, indicated that LamAT-Y is expressed both in promastigotes and axenic amastigotes at relatively equivalent levels based on the amount of input RNA in each reaction. As a control, we examined the expression of P-4 nuclease [35], whose expression is upregulated in amastigotes (Figure 1C). …”
Section: Resultsmentioning
confidence: 99%